FAKTOR-FAKTOR YANG MEMPENGARUHI ANAK PUTUS SEKOLAH ( STUDI : DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU) - Yessy Herawati; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of this study is to provide an overview of the characteristics of dropouts family and gives an overview of the factors that affect children out of school in District Tenayan Raya. Basic research used data from the Department of Education on the number of children dropping out. the type of research is descriptive quantitative research is research that works with numbers further analyzed using statistics in accordance with the reality described. The collection of data through observation and interviews directly to respondents. Sampling technique in this study using census method where the number of respondents there are only 31 people. The data has been collected from the results of the study were processed using a frequency table with family that the characteristics of achievement. Research shows children out of school in District Tenayan Raya most are boys aged 13-15 years. Large a proportion of ethnic families of school children is followed by the ethnic Batak ethnic Minang, Javanese and Malay. Day-to-day activities of school children are at home and that is to help parents work for a living to meet the economic needs of the family and school dropouts in this study are by and large have family members and peers who dropped out sekolah.Sedangkan factors influencing the dropout is a factor economic, family, school, academic ability, and accessibility factors and ways toward school. Among these factors, the factors that most affect the dropout is the economic factor family and peer influence, to minimize the number of school dropouts would rate the government charging a special scholarship for school dropouts and provide transportation for school children as well as costs the. In the government is expected to provide information about the importance of school and provide skills training for children who have dropped out of school.Keywords: Dropout, Factor Dropout, Child Dropout